2004
DOI: 10.1042/cs20040130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischaemic preconditioning on hepatic oxygenation, microcirculation and function in a rat model of moderate hepatic steatosis

Abstract: IPC (ischaemic preconditioning) may protect the steatotic liver, which is particularly susceptible to I/R (ischaemia/reperfusion) injury. Hepatic steatosis was induced in Sprague-Dawley rats with a high-cholesterol (2%) diet for 12 weeks after which rats were subjected to I/R (ischaemia/reperfusion; 45 min of lobar ischaemia followed by 2 h of reperfusion). Rats were divided into three study groups (n=6 each) receiving: (i) sham laparotomy alone, (ii) I/R, and (iii) IPC (5 min of ischaemia, followed by 10 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 52 publications
(59 reference statements)
2
30
0
Order By: Relevance
“…Two studies with rat models of IR-induced liver injury have shown that IPC has some protective effect against IR injury in fatty livers, possibly by reducing necrosis and improving hepatic circulation (4,131). In a subgroup analysis of patients undergoing major liver resection with or without IPC, obese patients with fatty livers seem to benefit the most from IPC (102).…”
Section: From Those Of Normal Livers?mentioning
confidence: 97%
“…Two studies with rat models of IR-induced liver injury have shown that IPC has some protective effect against IR injury in fatty livers, possibly by reducing necrosis and improving hepatic circulation (4,131). In a subgroup analysis of patients undergoing major liver resection with or without IPC, obese patients with fatty livers seem to benefit the most from IPC (102).…”
Section: From Those Of Normal Livers?mentioning
confidence: 97%
“…7,8 There is some evidence in isolated hepatocytes and experimental models of perfused liver that mitogen-activated protein kinases (MAPKs) are involved in the protective mechanisms of ischemic preconditioning. 9,10 Signaling pathways involved in HSP induction include MAPKs.…”
Section: 4mentioning
confidence: 99%
“…Choukér et al, 28 in a randomized clinical trial involving 68 patients, demonstrated that IP attenuated the hemodynamic effect of liver infl ow occlusion and reduced the need for intraoperative vasopressor therapy. The same authors, evaluating α-glutathione S-transferase as an early marker of hepatic I/R injury after liver resection, postulated that postoperative liver dysfunction could be 19 2005 Fatty rat liver 5I+10R 40 ↓ AST levels Selzner 20 2007 Older mouse 60 IP not protective against I/R injury in older mice Schiesser 21 2008 Older rat 10I+10R, 5I+10R 45 IP less effective than intermittent clamping against I/R injury IP, ischemic preconditioning; I, ischemia; R, reperfusion; ↑, increase; ↓, reduction; TNF-α, tumor necrosis factor alpha; LDH, lactate dehydrogenase; IL-6, interleukin-6; AST, aspartate aminotransferase; I/R, ischemia/reperfusion injury prevented by IP. 29 Nuzzo et al, 30 in a prospective randomized clinical trial of 42 patients, also confi rmed the hepatoprotective role of IP.…”
Section: Mechanical Preconditioningmentioning
confidence: 96%